A study on Fast Fourier Transform (FFT) and its implementation in image processing / Nor Ashikin Mohamad Kamal - Mohamad Kamal, Nor Ashikin (2002)
Image processing is not a new phenomenon. Computer-based image processing systems have become increasingly widespread over the past decades. Computers are used not only to collect information in a form of a digital image but also to improve the visual appearance of images to prepare images for the next processes. Techniques for the manipulation and enliancement of digital images have been practiced for over tliirty years. Now, image processing has insinuated itself into many areas of human endeavor such as medical and astronomy. This project is to study about Fast Fourier Transform method used in image processing. At the end of the research, an understanding of how this method is applied in image processing will be achieved. The report is based on secondary sources from the Internet, books, articles and magazines.